Detection of human insulin‐like growth factor‐1 in deer antler velvet supplements. (2nd September 2013) - Cox, Holly D.; Eichner, Daniel
<x xml:space="preserve">Abstract</x> RATIONALE Reported incidents of the use of nutritional supplements containing deer antler velvet by athletes has increased significantly in recent years. The supplements have been reported to contain insulin‐like growth factor‐1 (IGF‐1), which is a banned substance included on the World Anti‐Doping Agency (WADA) prohibited list. The presence of deer and human IGF‐1 was tested in six commercially available supplements. METHODS IGF‐1 was extracted from the six deer antler velvet supplements using chloroform and acetonitrile precipitation methods. Ultra‐performance liquid chromatography/tandem mass spectrometry (UPLC/MS/MS) methods were developed to measure intact IGF‐1 protein and IGF‐1 trypsin peptides using a triple quadrupole mass spectrometer. Five deer‐specific and five human‐specific multiple‐reaction monitoring (MRM) transitions for intact IGF‐1were measured as well as six deer‐specific and seven human‐specific MRM transitions for an IGF‐1 trypsin peptide. RESULTS The peak area from each MRM transition was used to calculate the product ion ratios relative to the most abundant transition. Product ion ratios measured in the supplements were matched to ratios measured in purified protein standards. A match to human IGF‐1 was identified for all the MRM transitions measured in four of the supplements tested. CONCLUSIONS The presence of a pharmaceutical protein, human IGF‐1, was confirmed in four commercially available products sold as all natural, nutritional supplements. These methods can be used to screen additional products to further prevent the illegal sale of adulterated supplements. Copyright © 2013 John Wiley & Sons, Ltd.